Peran Pimpinan Pondok Pesantren dalam Meningkatkan Penyelengaraan Mutu Pendidikan - Yusra; Junaidi (Jurnal Ilmiah Edukatif, 2024)
Islamic boarding school leaders are the driving force for Islamic boarding school resources. The large role of Islamic boarding school leaders in the process of achieving educational goals means that it can be said that the success or failure of Islamic boarding school activities is largely determined by the quality of the Islamic boarding school leaders themselves. The purpose of this article is to determine the role of Islamic boarding school leaders in improving the quality of education. This research uses library research methods (library research), namely deepening, reviewing and identifying knowledge contained in the literature (reading sources, reference books or other research results). To obtain data the author used sources found in libraries such as books, journals and the internet. The research results show the role of Islamic boarding school leaders in improving the quality of education, namely; Improving the quality of human resources for educators and education personnel, improving the quality of the teaching and learning process, educational facilities and infrastructure.